Achieving the Tridharma of Private Islamic Higher Education in Jambi Province Through an Internal Quality Assurance System - Masruri, M; Syukri, Ahmad; Us, Kasful Anwar (Yayasan Sembilan Pemuda Indonesia, 2024)
The research aims to find out about the internal quality guarantee system in tri dharma achievement at the private institute Islamic University of Jambi Province. The study was carried out at the Institut Agama Islam (IAI) YASNI Bungo, IAI Nusantara Batanghari, and IAI Muhammad Azim Jambi. This type of study is known as qualitative case study research. In this study, data was gathered through participant observation, in-depth interviews, and documentation. Data analysis is accomplished by gathering data, reducing data, presenting data, and verifying/ drawing conclusions. The results of the research are that the implementation of an internal quality assurance system at private Islamic Universities in Jambi Province is carried out by LPM leaders. to fulfill the tri dharma of private Islamic higher education in Jambi Province, the internal quality assurance system faces the following challenges: a) inadequate staff and lecturer human resources; b) unfulfilled standards for facilities and infrastructure; and c) a lack of innovation among students. In the meantime, the approach is to a) form partnerships with relevant stakeholders; b) look for support and availability for the acquisition of infrastructure and facilities; and c) enhance seminar instruction to advance students’ abilities.